Polybenzimidazole and its use in HT PEMFC, flow batteries, alkaline and AEM water electrolyzers - Dirk Henkensmeier (Max Planck Institute for Solid State Research, 2021)
Polybenzimidazole (PBI) is a versatile polymer. In contact with acids or bases, it becomes ion conductive. Therefore, it can be used at different pH conditions, opening a broad range of opportunities.[1] We will show the use of PBI in several applications: High Temperature Polymer Electrolyte Fuel Cells (HT PEMFC):[2] A blend of PBI with a tetrazolecontaining polymer showed a conductivity of 195mS/cm at 160°C (PBI: 147mS/cm) after doping in phosphoric acid. In the HT PEMFC, the membrane was tested successfully for over 2400h. 2000h of that were at 800mA/cm2 . The performance was not only high, but also very stable, with a voltage loss of just 27.7？V/h. Vanadium Redox Flow Batteries (VRFB): PBI doped with sulfuric acid has a low conductivity of
Keywords: water electrolysis; Polybenzimidazole; PBI; electrospinning; pore filling; HT PEMFC; fuel cell; VRFB; flow battery